Search for heavy isosinglet neutrinos in e+e- annihilation at 130 < √s < 189 GeV - Dova, María Teresa (1999)
A search for heavy neutrinos that are isosinglets under the standard SU(2)L gauge group is made at center-of-mass energies 130 < √s < 189 GeV with the L3 detector at LEP. Such heavy neutrinos are expected in many extensions of the Standard Model. The search is performed for the first generation heavy singlet neutrino, Ne , through the decay mode Ne→e+W. We set upper limits on the mixing parameter between the heavy and light neutrino for the heavy neutrino mass range from 80 GeV to 185 GeV.